MEDIA AJAR FLIPBOOK OBJEK WISATA SEJARAH KABUPATEN TEGAL UNTUK PEMBELAJARAN MENULIS TEKS DESKRIPSI - Kukuh Andriawan Sulistio Putra; Ika Septiana; Sudaryono (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Pancasakti Tegal, 2025)
The objectives contained in this study, the general objective of developing this teaching media is to produce Indonesian language teaching media for writing descriptive texts at the junior high school level that can be accessed on gadgets or PCs. Students who are accustomed to accessing gadgets or PCs to find references in doing assignments, often find texts that are not quite right in their writing. Therefore, students need to be given teaching media that can inspire them in writing texts on platforms on the internet, especially in writing descriptive texts. In addition to being able to write descriptive texts well and correctly, they also gain knowledge related to historical places in Tegal Regency. The results of students' learning to write descriptive texts were higher after using teaching media. These results are reinforced by the results of the hypothesis test which rejects Ho because t count> t table. Based on the results obtained in this study, the researcher makes a suggestion, namely that this study produces digital teaching media that is very good and easy to use in learning to write descriptive texts. This teaching media can be used, both independently and in the face-to-face learning process in the classroom. However, researchers who are interested in continuing this research can make improvements by utilizing more interesting and more sophisticated supporting platforms that are easy to access and to increase the effectiveness of teaching media, researchers need further research with more research subjects so that the results obtained are more valid.